Pediatric autoinflammatory bone disorders—a mini review with special focus on pathogenesis and inborn errors of immunity - Hetrick, Rebecca; Oliver, Melissa (Frontiers in Pediatrics, 2023)
Autoinflammatory bone disorders are a group of diseases characterized by sterile osteomyelitis. This includes chronic nonbacterial osteomyelitis and the monogenic forms, Majeed syndrome and deficiency of the interleukin-1 receptor antagonist. These disorders result from innate immune system dysregulation and cytokine imbalance that triggers inflammasome activation causing downstream osteoclastogenesis and excessive bone remodeling. In this review, we will summarize the immunopathogenesis of pediatric autoinflammatory bone diseases with a special focus on the genetics and inborn errors of immunity, while briefly touching on the clinical manifestations and management of each disease as well as areas for future research.